2003
DOI: 10.1159/000068392
|View full text |Cite
|
Sign up to set email alerts
|

Seed Dispersal by Sympatric Tamarins, Saguinus mystax and Saguinus fuscicollis: Diversity and Characteristics of Plant Species

Abstract: In a comparative study of Saguinus mystax and Saguinus fuscicollis, we examined the spectrum of plant species whose seeds are dispersed by these two tamarin species. We characterize these plants in terms of life form, fruit colour, pulp consistency and seed dimensions. The tamarins disperse a much broader spectrum of plant species than previously reported (88 of the total of 155 species exploited for fruit). While the distribution over plant life form, fruit colour and pulp consistency is identical between dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 42 publications
7
72
3
Order By: Relevance
“…Studies with small tamarins found the greatest number of 13 seeds passed by a captive moustached tamarin (Saguinus mistax) and six seeds passed by a saddle-back tamarin (S. fuscicollis) [10]. Other studies with these two primates found a variation between 1 and >4,800 seeds per fecal sample (including feces with seeds <3mm not considered in the present study) [24]. In this study we did not consider the number of seeds < 3mm in feces, but we used the number of fruits of Miconia latecrenata consumed by one group of tamarins in a preview study [33] and extrapolated it to estimate the number of seeds < 3 mm ingested by the tamarins.…”
Section: Pattern Of Feces Deposition and Deposition Sitescontrasting
confidence: 46%
See 1 more Smart Citation
“…Studies with small tamarins found the greatest number of 13 seeds passed by a captive moustached tamarin (Saguinus mistax) and six seeds passed by a saddle-back tamarin (S. fuscicollis) [10]. Other studies with these two primates found a variation between 1 and >4,800 seeds per fecal sample (including feces with seeds <3mm not considered in the present study) [24]. In this study we did not consider the number of seeds < 3mm in feces, but we used the number of fruits of Miconia latecrenata consumed by one group of tamarins in a preview study [33] and extrapolated it to estimate the number of seeds < 3 mm ingested by the tamarins.…”
Section: Pattern Of Feces Deposition and Deposition Sitescontrasting
confidence: 46%
“…Callitrichids have not figured prominently in studies of seed dispersal [10,[23][24][25][26][27][28] and more studies with seed dispersal by these small primates are therefore needed to understand their potential for contributing to the natural regeneration of undisturbed and disturbed forests [24].…”
Section: Introductionmentioning
confidence: 99%
“…By mediating the dispersal of a majority of large-seeded fleshy-fruited canopy tree species, large vertebrate frugivores are crucial in maintaining biodiversity and regeneration dynamics in tropical forests (Janzen, 1970;Connell, 1971). Smaller non-targeted species, even with increased abundance, cannot adequately replace the dispersal function of larger ones due to inherent anatomical and physiological limitations (Peres and Van Roosmalen, 2002;Poulsen et al, 2002;Knogge and Heymann, 2003;Stoner et al, 2007). Under high hunting pressure, tree species most reliant on large frugivores may experience substantially reduced recruitment, which can dramatically alter forest regeneration processes at the community level Nuñez-Iturri et al 2008;.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…The retention of the fluid portion of digesta, containing the complex polysaccharides from gums, has since been demonstrated in captive common marmosets (Caton et al 1996), although this ability to retain digesta may be lacking in non-specialist gummivores such as the tamarins, particularly since they often swallow large seeds that may impede retention of any part of the digesta (see Garber 1986, Garber andKitron 1997;Oliveira and Ferrari 2000;Knogge and Heymann 2003). In addition to benefits from consuming gums later in the day there are also potential costs of consuming them earlier.…”
Section: Patterns Of Gummivory Across the Daymentioning
confidence: 99%